CRIMINAL LAW ANALYSIS OF HEALTH SERVICE PRACTICES CARRIED OUT BY NON-HEALTH CARE PERSONNEL - Ervia Intan Nuraini; Karlinae D. Bangas; Claudia Yuni Pramita; Yacob Ferdinan M (RADJA PUBLIKA, 2026)
Practice service health carried out by individuals without permit and not Health Workers still often occurs in society. Practice the cause risk for safety patients and violate provision law . Research This aim For analyze law criminal to practice service health services carried out by non- health workers. The methods used is study law normative with approach regulatory and conceptual . Research results show that actions the including action criminal Because done without legitimate authority . In​ drop criminal , the judge considers element error , consequence for the victims, as well as attitude defendant during trial . Enforcement law This expected can cause effect deterrent , protect society , and realize certainty law in the field service health .